Kearifan Lokal dalam Implementasi Cause Related Marketing untuk Keberlanjutan Bisnis - Dorien Kartikawangi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
ASEAN Economic Community (AEC) is going to be a great opportunity and yet challenges for any business practices. The market integration provides possibilities to develop the business; however, the intercultural aspect would be another challenge. This study is analyzing the global marketing strategy and implementation for any corporation in taking advantage of an opportunity and overcome the obstacles. Theories on marketing and corporate communications are used as the research fundamentals. The research uses a qualitative research method according to find the answers to the case. Secondary data, depth interviews, and literature study become the source of triangular data analysis which are divided into three steps of coding. The research shows that strategy and implementation which combines marketing communication and CSR, especially Cause Related Marketing, becomes one of the appropriate global marketing strategy and execution. Proper implementation in term of its capability to increase the brand engagement and to overcome the intercultural obstacle is the primary challenge in global marketing. Based on the result, as a practical recommendation, the development of strategy and implementation in cause-related marketing would be resourceful if the business is also emphasizing and involving the local wisdom.